2020
DOI: 10.3390/polym12112435
|View full text |Cite
|
Sign up to set email alerts
|

A Magneto-Hyperelastic Model for Silicone Rubber-Based Isotropic Magnetorheological Elastomer under Quasi-Static Compressive Loading

Abstract: A new magneto-hyperelastic model was developed to describe the quasi-static compression behavior of silicone rubber-based isotropic magnetorheological elastomer (MRE) in this work. The magnetization property of MRE was characterized by a vibrating sample magnetometer (VSM), and the quasi-static compression property under different magnetic fields was tested by using a universal testing machine equipped with a magnetic field accessory. Experimental results suggested that the stiffness of the isotropic MRE incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this regard, there have been some studies reporting the viscoelastic behavior of synthetic rubbers. [63][64][65][66][67][68][69][70][71][72][73][74][75] However, silicone rubbers have relatively poor mechanical performance, that is, low strength and low fatigue life, which is one of their most significant drawbacks. [57] On the other hand, it has been reported that natural rubber has high failure strain, superior fatigue properties, and good damping properties.…”
Section: Matrixmentioning
confidence: 99%
“…In this regard, there have been some studies reporting the viscoelastic behavior of synthetic rubbers. [63][64][65][66][67][68][69][70][71][72][73][74][75] However, silicone rubbers have relatively poor mechanical performance, that is, low strength and low fatigue life, which is one of their most significant drawbacks. [57] On the other hand, it has been reported that natural rubber has high failure strain, superior fatigue properties, and good damping properties.…”
Section: Matrixmentioning
confidence: 99%
“…Isotropic and anisotropic MREs were characterized for quasi-static magneto-hyperelastic mechanical properties [31], depending on the microscale modeling based on different magnetic particle lattice structures and the non-linear hyperelastic mechanical modeling based on the Neo-Hookean model and the first-order Ogden model. The quasi-static compressive properties of isotropic MREs under a vertical magnetic field were experimentally characterized [32], and the Ogden hyperelastic model based on the experimental results can accurately predict the compressive hyperelastic behavior. The non-linear magnetoelastic coupling behavior of MREs [33] was investigated using the coupled Yeoh hyperelastic mathematical model to analyze the hyperelastic features through experimental characterization.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, reported researches have mainly focused on characterizing the MR effect by performing the single/double lap shear test [1,[15][16][17][18], the rotational shear test [19][20][21], the compression test [22][23][24], and the tensile test [25,26]. Among those researches, rotational shear test by using the rotational rheometer equipped with an electromagnet accessory is quite popular on account of the straightforward experimental procedure.…”
Section: Introductionmentioning
confidence: 99%